Improving IPv6 Packets Transmission Over High Speed Networks By Introducing CRC Extension Header - Supriyanto, . (2010)

(untitled)
Utilizing the advantages of IPv6 features and high speed networks technologies on IPv6 packets transmission is believed will force the transmission to be faster. Thus, verification and regeneration of cyclic redundancy check (CRC) code in every router results in high network latency. This thesis attempts to decrease the network latency by eliminating CRC calculation in router using the advantage of IPv6 features itself. The CRC Extension Header (CEH) is introduced as a new IPv6 extension header to perform error detection in the Network layer. Generation of CRCcode requires a generator polynomial.